2015
DOI: 10.1590/0037-8682-0001-2015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of visceral leishmaniasis in the municipality of Rondonópolis, in the Brazilian State of Mato Grosso, from 2003 to 2012: human, canine and vector distribution in areas of disease transmission

Abstract: Introduction: Visceral leishmaniasis (VL) is a zoonosis of great importance to public health and is considered a neglected disease by the World Health Organization. The disease has expanded and become more prevalent in urban areas in Brazil. Methods: Geospatial analyses were performed and thematic maps of the triad of the disease were produced for the study period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) in the urban area of the municipality of Rondonópolis in the midwestern State of Mato G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…Our results corroborate those of other authors, who observed percentages of 39.8% to 56.7% for the same age group 7 , 10 , 11 . ACL is more important in the age group of economically active adults in comparison with visceral leishmaniasis, which affects higher percentages of children 12 . …”
Section: Discussionsupporting
confidence: 92%
“…Our results corroborate those of other authors, who observed percentages of 39.8% to 56.7% for the same age group 7 , 10 , 11 . ACL is more important in the age group of economically active adults in comparison with visceral leishmaniasis, which affects higher percentages of children 12 . …”
Section: Discussionsupporting
confidence: 92%
“…The current expansion of VL in Brazilian territories represents a clinical and epidemiological concern for public health authorities and health professionals, especially due to the complexity associated with its control and clinical management 1 , 4 , 8 . The State of Mato Grosso is historically endemic for VL 16 , with the municipality of Rondonópolis containing almost half of the human cases reported there in recent years, being an area of intense VL transmission with regional and national relevance 12 , 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this great importance, the area lacks studies regarding the disease occurrence. The only report described the spatial distributions of human cases, reservoirs and vectors 13 . Thus, the present study aimed to describe epidemiological and clinical aspects of the occurrence, VL/HIV coinfection and lethality of VL in the municipality of Rondonópolis between 2011 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…included in the work of Cardim et al (12) , Antonialli et al (13) , Martins-Melo et al (14) , and Guimarães et al (15) .…”
Section: Methodsmentioning
confidence: 99%